Development of a Multicultural Based Education Model in Social Studies Learning in the 21st Century in Indonesia - Rufaidah, Erlina; Kodri (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of this study are: 1) increasing the ability of junior high school teachers to plan, implement, and evaluate multicultural-based social studies learning, 2) the development of multicultural-based education models in social studies learning and 3) implementing multicultural-based education models in social studies learning. The approach of this research is Research and Development (R&D) consists of three stages of research. The first stage is the preliminary stage. The second stage of the development stage is to develop a multicultural-based education model in social studies learning. The third stage, the stage of implementing multicultural-based education models in social studies learning. The research subjects were teachers, principals, students, school committees, education and culture offices in the South Lampung Regency, who were selected by purposive sampling. Data collection used questionnaires, observations, interviews, and documentation studies, which were supported by notebooks and focus group discussions. Data analysis uses descriptive techniques. The results of the study are as follows: 1) the ability of teachers to understand multiculturalism can increase after there is socialization, 2) multicultural-based learning models are given integrated with Social Science (PKPS) learning with Socially Oriented Program (ScOP) approaches, 3) multicultural-based education models in social studies learning implemented in schools